Perfil de Antígona en la Antígona de Sófocles - García C., Héctor (Byzantion Nea Hellás, 2015)
The author propounds a detailed reading of Sophocles’ work Antigona. He settles the work previously in the sociocultural context of the Athens from the Golden Century, presenting an introduction about the modus vivendi of the woman from the Classic Athens, specially the role of teenage girl and generally the role of youngers in such a society. The author stands out that only under this context it is possible to apreciate in its whole magnitude the conflict within Sophocles’ Antigona. He analyses this work in its original structure, segmented in seven discursive moments to study how it is formed the profile of Antigona’ young women. Such analysis allows the author to find out that within Sophocles’ work there is a great gender conflict, presenting a real appraisal of women’s role in the structure of political power and society as well. That’s why the tragedy Antigona is an excentric and absolutely excontemporary work.